Brief Report: Six‐Week Treatment of Axial Spondyloarthritis Patients With an Optimal Dose of Nonsteroidal Antiinflammatory Drugs: Early Response to Treatment in Signal Intensity on Magnetic Resonance Imaging of the Sacroiliac Joints. Issue 3 (March 2016) - Varkas, G.; Jans, L.; Cypers, H.; Van Praet, L.; Carron, P.; Elewaut, D.; Van den Bosch, F.
Abstract : Objective: To evaluate the early effect of full‐dose nonsteroidal antiinflammatory drugs (NSAIDs) on the extent and intensity of bone marrow edema of the sacroiliac (SI) joints on magnetic resonance imaging (MRI) in axial spondyloarthritis (SpA). Methods: A single‐center, 6‐week study of a cohort of consecutive patients with clinically suspected axial SpA was conducted. A total of 117 patients were screened. Forty patients who were diagnosed as having axial SpA and had presented with a positive MRI of the SI joints as defined by the Assessment of SpondyloArthritis international Society (ASAS) criteria were considered for a followup MRI after 6 weeks of an optimal dose of NSAIDs. Twenty patients completed the study. Disease activity was monitored by determining the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) score every 2 weeks and the Bath Ankylosing Spondylitis Functional Index score at baseline and week 6. NSAID intake was assessed by the ASAS NSAID index. Primary end points were improvement in bone marrow edema of the SI joints on MRI and BASDAI response at week 6. Results: Approximately one‐third of eligible patients newly diagnosed as having axial SpA were unable to continue the full‐dose NSAID schedule. The median NSAID index was 97% in patients who completed the study. There was a reduction of 1.1 units (10.5%) in mean Spondyloarthritis Research Consortium of Canada (SPARCC) scores at week 6 in comparison to baseline ( P  = 0.032). Overall, only 30% of the patients (6 of 20) had a minimal clinically important difference of ≥2.5 in SPARCC score. However, 80% of the patients displayed high‐intensity lesions on STIR images at baseline, which decreased significantly at week 6 ( P  = 0.011). There was a significant decrease in the relative intensity of the region of interest ( P  = 0.007) and a mean decrease of 0.6 in the BASDAI score per 2 weeks of therapy ( P  = 0.001). Only 29.4% of the patients met the BASDAI criteria for 50% improvement (BASDAI50) at week 6. Conclusion: Our findings indicate a high level of dropout among patients receiving full‐dose NSAID therapy in daily practice. In those who tolerated NSAID therapy, there was no clinically relevant decrease in SPARCC scores and low BASDAI50 response. However, we found a decrease in signal intensity of bone marrow edema of the SI joints as an early response to 6 weeks of optimal NSAID therapy in patients newly presenting with axial SpA.